Methodological Tools for an Integral Evaluation of Strategic Financial Goals of the Commercial Organization - VLADIMIROVA, Tatyana A.; GRISCHENKO, Nataliya B.; NADEZDINA, Svetlana D. (Journal of Advanced Research in Law and Economics, 2017)
The problems of goal setting formalization in strategic financial management are discussed; the concept of an integral evaluation of achieving strategic financial goals is developed; a methodology of integrated indicative assessment of achieving financial goals of the organization is provided and its illustration on the example of the group of companies is given.